Catalogue of Iranian subfamily Galerucinae s. str. (Coleoptera: Chrysomelidae) - Mostafa Mirzaei; Jamasb Nozari (Iranian Journal of Animal Biosystematics, 2016)
The first comprehensive catalogue of leaf beetles (subfamily Galerucinae s. str.) from Iran is reviewed and several field trips were conducted from 2012 to 2015. In total, 44 species belonging to 18 genera of three tribes (Galerucini, Hylaspini and Luperini) are listed. Iranian Galerucinae is characterized by 11 endemic species. For every species provincial distributions is given based on available literature records and additional province records were examined. All species that deposited in Jalal Afshar Zoological Museum (University of Tehran) are reported. Moreover, Luperus perlucidus Iablokoff-Khnzorian, 1956 is reported as a new record for Iranian Chrysomelidae. Theone octocostata afghanistanica Mandl, 1968, Galerucella nymphaeae (Linnaeus, 1758), Galeruca pomonae (Scopoli, 1763), Exosoma thoracicum (Redtenbacher, 1843) and Luperus kiesenwetteri Joannis, 1865 which were omitted in the catalogue of Palaearctic Coleoptera added again to the leaf beetle fauna of Iran. In addition, 13 new records for the administrative provinces of Iran are provided.